SEBARAN DAN PRODUKSI KELOMPOK PEMBUDIDAYA IKAN AIR TAWAR DI KECAMATAN MUNTOK, BANGKA BARAT - Ira Triswiyana; Ayu Permatasari; Juandi Juandi (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
Freshwater fish farming in West Bangka Regency is developing to meet the needs of the local market. Information about the distribution and production of fish farmers groups (Pokdakan) can be used as a basis for planning sustainable development. This research was conducted using a survey method in July - September 2019 in Muntok District, West Bangka Regency. Fifteen Pokdakan scattered in seven villages with the majority developing catfish commodities. There is only one group that belongs to the middle class, while the other group is still in the beginner class. Freshwater fish productivity reaches 3.2 tons per quarter. The majority of Pokdakan utilize former tin mines with step-in-net cage for fish farming so that their productivity is affected by the season. Continuity of production is needed so that the class of Pokdakan can increase.